Corporate Responsibility for Environmental Damage from The Perspective of Unlawful Acts and Environmental Justice - Dahliani Dahliani; Hadi Tuasikal (Magister Hukum Universitas Semarang, 2025)
The purpose of this study is to analyze the application of the principles of unlawful acts and environmental justice to companies, obstacles to law enforcement, and the monitoring and enforcement system related to environmental damage in Indonesia. Environmental damage caused by corporate activities is a global issue. Companies often ignore ecological impacts, threaten biodiversity, and harm surrounding communities, requiring strict law enforcement. Law enforcement against companies that damage the environment in Indonesia faces major obstacles, such as a lack of effective supervision, corruption, and political influence, which hinder corporate responsibility for environmental damage. This study offers a novel perspective by focusing on the legal responsibility of perpetrators of land damage, moving beyond previous research that primarily discussed the government's right to sue for unlawful acts. This study uses a normative juridical approach with analysis of legal regulations, principles of corporate responsibility, and environmental justice, using secondary data analyzed qualitatively. The results indicate that corporate responsibility for environmental damage from the perspective of unlawful acts and environmental justice in Indonesia still faces obstacles. Although regulations govern corporate responsibility, applying the principles is ineffective due to political influence, corruption, and weak monitoring. Strengthening regulatory institutions, implementing transparent reporting systems, and imposing stricter sanctions on companies damaging the environment are important steps to ensure justice. Developed countries can serve as models for improving Indonesia’s law enforcement system.